4.1: Invited Paper: Electronic Structure, Carrier Transport, Defects and Impurities in Amorphous Oxide Semiconductor. Issue 1 (1st July 2013) - Kamiya, Toshio; Nomura, Kenji; Hosono, Hideo
Abstract This review paper provides the present status of amorphous oxide semiconductor technology along with knowledge obtained to date on their carrier transport, defects and impurities in relation to their stability issues.